The hedonic delights of frugality: Pound store shopping in austere times. (November 2019) - Hulme, Alison
This article explores the attitudes of pound store shoppers in the United Kingdom and the ways in which 'consumptive thrift' (spending to save) has become embedded in popular culture. Through an analysis of ethnography carried out in low-income urban areas with regular pound store shoppers, it argues that a culture of bargain seeking exists, which is unique to the current era. While in previous eras hedonic pleasures were acknowledged, including those of spontaneity and disposability, they were not dialectically linked to economic motivations in the same way as they now are. Factors such as frugality and 'saving' have made bargain stores a crucial feature in an economic climate that requires consumer spending but preaches individual economic responsibility. The bargain seeker's hedonic pleasures are therefore utilized by the State as part of strategic economic pathways through straightened times.